Persistence of Inflammatory Response to Intense Exercise in Diabetic Rats - Bortolon, J.; de Almeida Silva Junior, A.; Murata, G.; Newsholme, Philip; Curi, R.; Pithon-Curi, T.; Hatanaka, E. (Hindawi Publishing Corporation, 2012)
In this study we evaluated the onset and resolution of inflammation in control and streptozotocin-induced diabetic rats subjected to a single session of intense exercise. The following measurements were carried out prior to, immediately after, and 2 and 24 hours after exercise: plasma levels of proinflammatory cytokines (TNF-α, IL-1β, IL-6, CINC-2α/β, MIP-3α, and IL-6), immunoglobulins (IgA and IgM), acute phase proteins (CRP and C3), and creatine kinase (CK) activity. We also examined the occurrence of macrophage death by measurements of macrophages necrosis (loss of membrane integrity) and DNA fragmentation. An increase was observed in the concentration of IL-1β (3.3-fold) and TNF-α (2.0-fold) and in the proportion of necrotic macrophages (4.5-fold) in diabetic rats 24 hours after exercise, while the control group showed basal measurements. Twenty-four hours after the exercise, serum CK activity was elevated in diabetic rats but not in control animals. We concluded that lesion and inflammations resulting from intense exercise were greater and lasted longer in diabetic animals than in nondiabetic control rats.